2018
DOI: 10.1177/1077559518816381
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response and Children Re-Reported to Child Protective Services: County Data From the National Child Abuse and Neglect Data System (NCANDS)

Abstract: Child protection systems that implement differential response (DR) systems screen to route referrals to an investigation response (IR) or alternative response (AR). AR responses emphasize family engagement, assessment of family needs, and service linkage. Usually, AR state-level policy does not require child welfare staff to make a maltreatment determination. Jurisdictions implement DR systems differently, leading to variations in the proportion of AR cases, risk levels of cases served, and the ways families a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Further, there have been many evaluations (with comparison groups) of differential response (DR) programs, which provide a modicum of services in lieu of formal court-ordered services. Results have demonstrated that child safety, typically measured by report recurrence, substantiated rereport, or removal of a child from the home, is not significantly different than it is for those involved with more formal child welfare services (e.g., Fluke et al 2019; Fuller and Zhang 2017). Although many questions about DR remain, including the threshold of risk and level of utilization at which child safety can be maintained without court supervised services (Fluke et al 2019), a recent quasi-experiment in economics found states using DR experienced fewer victims and foster care entries over time when compared to states without the program (Johnson-Motoyama et al 2020).…”
Section: Services and Programs To Prevent Maltreatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, there have been many evaluations (with comparison groups) of differential response (DR) programs, which provide a modicum of services in lieu of formal court-ordered services. Results have demonstrated that child safety, typically measured by report recurrence, substantiated rereport, or removal of a child from the home, is not significantly different than it is for those involved with more formal child welfare services (e.g., Fluke et al 2019; Fuller and Zhang 2017). Although many questions about DR remain, including the threshold of risk and level of utilization at which child safety can be maintained without court supervised services (Fluke et al 2019), a recent quasi-experiment in economics found states using DR experienced fewer victims and foster care entries over time when compared to states without the program (Johnson-Motoyama et al 2020).…”
Section: Services and Programs To Prevent Maltreatmentmentioning
confidence: 98%
“…Results have demonstrated that child safety, typically measured by report recurrence, substantiated rereport, or removal of a child from the home, is not significantly different than it is for those involved with more formal child welfare services (e.g., Fluke et al 2019; Fuller and Zhang 2017). Although many questions about DR remain, including the threshold of risk and level of utilization at which child safety can be maintained without court supervised services (Fluke et al 2019), a recent quasi-experiment in economics found states using DR experienced fewer victims and foster care entries over time when compared to states without the program (Johnson-Motoyama et al 2020). The reductions in victims and foster care entries were causally related to the implementation of DR, suggesting DR may have an important role in secondary and tertiary prevention.…”
Section: Services and Programs To Prevent Maltreatmentmentioning
confidence: 98%
“…Case planning with families in situations of poverty may also benefit from more appropriate services to address their particular needs (e.g., Loman, 2006). For example, differential response models offer a more flexible practice approach depending on family needs and are unsurprisingly shown to attend well to situations of poverty and gaps in material wellbeing (Delaye & Sinha, 2017;Fluke et al, 2019;Loman, 2006;Loman & Siegel, 2012). Both now and going forward, we urge child protection systems to consider how risk and chronic need are being considered and integrated into decision making during assessment, case planning, intervention, and case closure, and to question how well this can be done "virtually" without proximity to families and their environments.…”
Section: Long-term Outcomes: Balancing Immediate Risk and Chronic Needmentioning
confidence: 99%
“…Families screened out following a maltreatment report or whose report does not result in an open case are sometimes referred to community-based programs (e.g., after-school programs, parent support groups, youth diversion programs). Other dispositions include placement of a family case in an alternative or differential response track, which allows for a less intrusive level of involvement with families whose children have been deemed to be at low or moderate risk for future harm (Fluke et al 2019; Hughes et al 2013). In these cases, next steps typically include voluntary acceptance of CPS services contracted to community agencies, based on specific familial needs.…”
Section: The Cps Processmentioning
confidence: 99%